THE MEDIATING ROLE OF ORAL READING FLUENCY AND THE SUPPORTING EFFECT OF VOCABULARY KNOWLEDGE IN THE RELATIONSHIP BETWEEN PHONOLOGICAL AWARENESS AND READING COMPREHENSION: A CONCEPTUAL STUDY - Li , Lijing; Shak , Priscilla (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The primary aim of this study is to explore how Chinese English as a Foreign Language (EFL) learners’ reading comprehension (RC) proficiency can be effectively enhanced through the interrelated constructs of Phonological Awareness (PA), Oral Reading Fluency (ORF), and Vocabulary Knowledge (VK). Although previous research indicates that PA does not always exert a direct influence on reading comprehension, it remains a foundational cognitive skill that facilitates accurate decoding and phoneme manipulation. This study therefore proposes a context-sensitive conceptual framework specifically designed for the Chinese EFL context, where learners’ logographic first language often constrains their sensitivity to phonological structures in English. Within this framework, PA functions as the independent variable, reading comprehension as the dependent variable, and ORF serves as a mediating construct that transforms decoding competence into fluent text processing. VK is conceptualized as a supporting or moderating path, strengthening the connection between phonological decoding and semantic comprehension. The study is conceptually based on the validated self-perception frameworks to maintain theoretical rigor and contextual relevance. The findings are expected to enrich the theoretical understanding of the mechanisms underlying EFL reading comprehension and to practice evidence-based instructional strategies that integrate phonological training, fluency practice, and vocabulary development within the Chinese educational context.